INTEGRATION OF AI IN ISLAMIC EDUCATION: ETHICAL OPPORTUNITIES AND CHALLENGES - Mukarom, Zaenal; Heriyanto, Imron; Hermansyah, Yus; Baehaqi, Anan; Yudiyanto, Mohamad; Setiawan, Budi (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
The study discusses the integration of artificial intelligence (AI) in Islamic education, with a focus on emerging ethical opportunities and challenges. AI offers a variety of opportunities in enriching the learning experience, such as adaptive learning, personalized education, and access to science globally. However, the application of AI also raises a number of ethical questions related to privacy, dependence on technology, and the potential for algorithmic bias that can affect Islamic values. This research uses a qualitative approach, by reviewing related literature and case studies of AI implementation in Islamic educational institutions. The findings suggest that while AI can improve the effectiveness of education, a strong ethical framework is needed for its application to be in line with the principles of Islamic teachings. Thus, this research offers an important perspective for policymakers, educators, and technology developers in integrating AI responsibly in the Islamic education environment.